2016
DOI: 10.1016/j.ijporl.2016.04.040
|View full text |Cite
|
Sign up to set email alerts
|

A novel biallelic splice site mutation of TECTA causes moderate to severe hearing impairment in an Algerian family

Abstract: Congenital deafness is certainly one of the most common monogenic diseases in humans, but it is also one of the most genetically heterogeneous, which makes molecular diagnosis challenging in most cases. Whole-exome sequencing in two out of three Algerian siblings affected by recessively-inherited, moderate to severe sensorineural deafness allowed us to identify a novel splice donor site mutation (c.5272+1G > A) in the gene encoding α-tectorin, a major component of the cochlear tectorial membrane. The mutation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 46 publications
0
9
1
Order By: Relevance
“…This HL deterioration rate is comparable to the hearing deterioration rate in a normal hearing control population. A previous report stated that patients with TECTA -associated mid-frequency HL might be prone to presbycusis as they are theoretically exposed to a lower level of sound energy as a result of cochlear amplification deficiency [36,37]. However, our results indicated that the hearing loss progression rate was the same as in the control group.…”
Section: Discussioncontrasting
confidence: 71%
“…This HL deterioration rate is comparable to the hearing deterioration rate in a normal hearing control population. A previous report stated that patients with TECTA -associated mid-frequency HL might be prone to presbycusis as they are theoretically exposed to a lower level of sound energy as a result of cochlear amplification deficiency [36,37]. However, our results indicated that the hearing loss progression rate was the same as in the control group.…”
Section: Discussioncontrasting
confidence: 71%
“…Pre-lingual hearing impairment was common in our study population which agrees with other findings (Chibisova et al, 2018). Majority of pre-lingual HI are congenital and are usually caused by genetic factors (Wonkam et al, 2013; Behlouli et al, 2016). Waardenburg syndrome was the most common syndromic HI identified among the congenital cases in line with other African data (Noubiap et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Recessively inherited defects of TECTA can cause moderate-tosevere HI, although with a more flat audiogram configuration than observed in the presented families. 38,39 We scrutinized TECTA for defects in family W05-682, and we excluded (potentially) causative variants in the exonic sequences and splice sites of the gene. We did not obtain any indication for aberrant splicing that might result from deep intronic variants.…”
Section: Discussionmentioning
confidence: 99%